The impact of insolvency on corporate contracts: a comparative study of the UK and US insolvency law regimes - Udofia, Kubianga Michael (2014)
Parties who contract at arm’s length are bound by the terms of their contracts, provided the contracts do not contravene a rule of law or public policy. The commencement of formal insolvency proceedings may however limit the ability of a debtor to perform its pre-petition contractual obligations, resulting to liabilities to creditors. Accordingly, a formal insolvency procedure ensures an orderly and efficient resolution of the debtor’s affairs -- maximising realisations to creditors or rescuing the corporate debtor as a going concern. To achieve this purpose, unilateral contract enforcement efforts and rights are replaced by a mandatory regime characterised by collectivity and equality in treatment of similarly situated creditors. This thesis comparatively evaluates the impact of the commencement of formal insolvency proceedings on corporate contracts in the UK and US. It examines the extent to which pre-petition contractual bargains are suspended, adjusted or avoided by the supervening insolvency law regime in the jurisdictions. The thesis adopts a thematic approach to examine how the legal frameworks in the jurisdictions manage the inevitable conflict between the policy considerations of contract law and those of insolvency law. The extent to which insolvency law should interfere with pre-insolvency contractual arrangements and entitlements has always been a contentious and keenly debated issue. No doubt, insolvency law has a greater number of interests to protect outside the interests of pre-petition contracting parties. These include the general body of creditors, employees, post-petition creditors etc. Nevertheless, in the absence of compelling and well-articulated policy justification, formal insolvency ought not to be a forum for the stripping of property rights or the pursuit of redistributional goals.